The Role of Family in Caring for Critically Ill Children in the Intensive Care Unit: A Narrative Review - Sri Hendrawati; Nenden Nur Asriyani Maryam; Windy Rakhmawati; Septa Permana (HealthCare Nursing Journal, 2025)
Critically ill children admitted to intensive care units experience complex physical and emotional challenges, not only for themselves but also for their families. Family-centered care (FCC) has become a cornerstone in children's critical care, emphasizing collaboration, respect, and shared decision-making between healthcare teams and families. Despite growing recognition of its benefits, the practical roles of families in children's intensive care unit settings remain diverse and sometimes underutilized across different healthcare systems and cultural contexts. This research aims to identify the family's role in caring for critically ill children in the intensive care unit. This research method uses narrative review. Articles were collected from Pubmed, ScienceDirect, EBSCOhost, and Google Scholar. The keywords used were critically ill children OR children in PICU OR children in NICU AND family involvement OR role of family OR family participation OR family-centred care OR FCC AND intensive care unit OR critical care with boolean "OR" and "AND". Inclusion criteria were free full-text, years of publication between 2020-2025, and articles in Indonesian or English. The search results obtained 11.345 articles, and only 10 articles met the criteria, which were then analyzed. Across various studies, families, particularly parents, emerged as essential components in the care of critically ill children. Their roles extended beyond traditional caregiving and encompassed several interconnected domains: emotional support and security, physical and emotional presence, advocacy and care partnership, participation in daily care, communication and shared decision-making, creating a sense of home and normalcy, coping and post-discharge involvement. Families contribute not only emotional and physical support but also advocacy, caregiving participation, and partnership in decision-making, all of which enhance patient outcomes and support holistic care delivery. Nurses are pivotal in operationalizing family-centred care principles and ensuring meaningful family involvement in caring for critically ill children in the intensive care unit.